Improvement in appropriateness and diagnostic yield of fast-track endoscopy during the COVID-19 pandemic in Northern Italy - Manes, Gianpiero; Saibeni, Simone; Pellegrini, Lucienne; Picascia, Desiree; Pace, Fabio; Schettino, Mario; Bezzio, Cristina; de Nucci, Germana; Hassan, Cesare; Repici, Alessandro; and The Fast-Track Endoscopy Study Group (Endoscopy, 2020)
Background During the COVID-19 outbreak in Italy, only fast-track endoscopic procedures have been performed; nevertheless, a significant drop in their number has been reported. We evaluated whether the pandemic has impacted the appropriateness and diagnostic yield of fast-track endoscopic procedures compared with those performed in 2019.Methods This retrospective study involved endoscopy services in Northern Italy. We compared data regarding endoscopic procedures performed in March and April 2020 with those performed during the same period in 2019.Results In 2020, there was a 53.6 % reduction in the number of fast-track endoscopic procedures compared with 2019. Patients undergoing endoscopy in 2020 were younger than in 2019. Both appropriate referral and diagnostic yield increased in 2020 for both upper and lower endoscopy. A higher rate of cancer was diagnosed in 2020 by upper endoscopy (3.6 % vs. 6.6 %; P = 0.04).Conclusions The high level of inappropriate endoscopy referrals registered in 2019 significantly improved during the COVID-19 outbreak of 2020, with an increase in the diagnostic yield.